Feeding of smoothtongue Leuroglossus schmidti in the Bering, Okhotsk Seas and adjacent waters of the Pacific Ocean - Alexander Ya. Efimkin (Известия ТИНРО)
Smoothtongue Leuroglossus schmidti is a small mesopelagic fish species common for subarctic waters. It rises to the upper epipelagic layer at night for feeding and preys mainly on euphausiids, copepods and amphipods. Its mean index of stomach fullness reaches 68 ‱ in the epipelagic layer, but it almost doesn’t feed deeper than 200 m, judging by a little food in the stomach. In the Bering Sea, euphausiids dominate in its diet and the portion of copepods is small. In the ​​Okhotsk Sea, each of these two groups provides a half of the diet. In the North Pacific, the portion of copepods is 63 % on average, euphausiids are the second important prey, and amphipods occur in the diet occasionally. Daily ration of smoothtongue is about 1.4 %.